DIGITAL LEADERSHIP CAPABILITY EFEKTIF MENINGKATKAN EMPLOYABILITY KARYAWAN SEKTOR JASA - Wardani, Yulinda Siti; Ingsih, Kusni; Febriana, Artha; Purusa, Nanda Adhi (POLITEKNIK LP3I JAKARTA, 2026)
The rapid digital transformation requires companies in the service sector to develop human resources (HR) who are innovative, adaptable, and highly competitive. Using Self-Efficacy as a mediating variable, this study aims to analyze the influence of Digital Leadership Capability and Innovation Capability on the value or level of employee Employability in the service subsector in the City of Semarang. The analysis is based on the Resource-Based View (RBV) theory, which emphasizes the importance of internal resources in building long-term competitive advantage. The study population consists of all employees in the service sector in Semarang, with 150 employees selected as samples using purposive sampling based on specific criteria. A quantitative approach is employed using PLS-SEM through the SmartPLS 3.2.9 software. The research findings reveal that Digital Leadership Capability and Innovation Capability have positive and significant effects on both Self-Efficacy and Employability. Additionally, Self-Efficacy is proven to play a significant mediating role in the relationship between the two independent variables and employee work capability. These conclusions demonstrate that digital leadership capability, innovation capability, and self-efficacy are strategic intangible resources that play an essential role in building the competitive advantage of both employees and companies in an increasingly digital business environment.